The final discharge: Quantifying contaminants in embalming process effluents discharged to sewers in ontario, Canada. (September 2019) - Kleywegt, Sonya; Payne, Mark; Raby, Melanie; Filippi, Daniel; Ng, Chi-Fai; Fletcher, Tim
Abstract: The process of embalming human remains as part of the funeral home industry, entails replacing blood with embalming fluid. Typically the unused/excess fluids are disposed of directly to the sewershed or septic system. The presence of select contaminants in sewer discharges from 8 funeral homes (facilities) in York Region, Ontario during active embalming processes was studied. A wide range of contaminants including embalming fluids (formaldehyde and triclosan); metals, conventional parameters, persistent organic pollutants (polycyclic aromatic hydrocarbons, pesticides, and polychlorinated byphenyls), nonyl phenols and active pharmaceutical ingredients (APIs) were measured in the final embalming effluent and compared to regulatory sewer limits where available. Two main constituents of embalming fluids—formaldehyde and triclosan—were detected at maximum concentrations of 561, 000 μg/L and 505 μg/L respectively. Other persistent organic pollutants detected in embalming effluent included banned pesticides lindane (83 ng/L) and metabolites of DDT (DDE; 2, 300 ng/L). Elevated APIs found in over-the-counter drugs and products were also frequently detected at elevated concentrations (oxybenzone, hydrocortisone, lidocaine, naproxen, ibuprofen, ciprofloxacin and DEET). Most contaminants did not exceed regulatory sewer limits where available, however others including biochemical oxygen demand (cBOD5 ) and conventional parameters were consistently above regulatory limits. Large amounts of formaldehyde and triclosan may pose a risk to receiving sewersheds and receiving sewage treatment plants due to their antimicrobial activities. Graphical abstract: Image 1 Highlights: Funeral homes are a source of contaminants to the aquatic environment during embalming processes. Formaldehyde and triclosan are detected at elevated concentrations in funeral home effluents. Onsite treatment for effluents should be considered to reduce risk to the receiving environment.